Revolutionizing Economics Learning in High School: Insights from the Flipped Classroom Approach - Allen A. Ch. Manongko; Sahat Renol HS; Selvita Eka Eviana Purba (Economics Education Department Universitas Negeri Semarang, 2025)
The study of Economics, particularly taxation, is often perceived as difficult because it requires an understanding of abstract concepts and technical calculation skills. Conventional teacher-centered instructional models tend to limit students' opportunities to build their own understanding actively. This study aims to examine the effectiveness of the flipped classroom (FC) model in improving student learning outcomes in Taxation. A quasi-experimental design with a non-equivalent control group pretest–posttest was used in this research. The sample consisted of 68 eleventh-grade students at XYZ Public High School in North Sulawesi, divided into an experimental group (FC) and a control group (traditional learning). Data were collected through pre-tests and post-tests and analyzed using ANCOVA, effect size, and N-Gain scores. The ANCOVA results, controlling for pretest scores, showed that the flipped classroom model led to better learning outcomes compared to traditional instruction. The FC model effectively strengthened students' cognitive abilities and practical skills through independent and collaborative learning activities. Practically, teachers need to prepare engaging digital content and contextual assignments so that the flipped classroom can serve as a relevant strategy to enhance the quality of Economics education at the senior high school level.